Experimental investigation and modeling of fuel wall films from gasoline direct injection nozzles - Da Silva Cruz Lis, Vanessa; Samenfink, Wolfgang; Schünemann, Erik; Wensing, Michael (ICLASS 2021 - 15th Triennial International Conference on Liquid Atomization and Spray Systems, 2021)
The reduction of fuel wall films is necessary to limit particulate emissions in combustion engines. Especially under cold conditions and load steps, the developing wall films might not evaporate completely before the start of combustion. The investigation of fuel wall films is the basis for understanding the parametric conditions that promote wall film formation caused by multi-hole direct injection nozzles. Fundamental experiments are described in this work with two different measurement techniques to collect data on wall film parameters under a large set of surrounding conditions. The results of these experiments are discussed and compared to the results of an adapted wall film evaporation model from the literature. The differences to the measurements and the limitations of the model and their causes are considered.
CRIS-Team Scopus Importer:2024-12-16
Keywords: fuel wall films; gasoline direct injection; particulate emissions